Immobilized TiO(2) on glass spheres applied to heterogeneous photocatalysis: photoactivity, leaching and regeneration process - Cunha, Deivisson Lopes (PeerJ, 2018)
Heterogeneous photocatalysis using titanium dioxide as catalyst is an attractive advanced oxidation process due to its high chemical stability, good performance and low cost. When immobilized in a supporting material, additional benefits are achieved in the treatment. The purpose of this study was to develop a simple protocol for impregnation of TiO(2)-P25 on borosilicate glass spheres and evaluate its efficiency in the photocatalytic degradation using an oxidizable substrate (methylene blue), in a Compound Parabolic Concentrator (CPC) reactor. The assays were conducted at lab-scale using radiation, which simulated the solar spectrum. TiO(2) leaching from the glass and the catalyst regeneration were both demonstrated. A very low leaching ratio (0.03%) was observed after 24 h of treatment, suggesting that deposition of TiO(2) resulted in good adhesion and stability of the photocatalyst on the surface of borosilicate. This deposition was successfully achieved after calcination of the photocatalyst at 400 °C (TiO(2)-400 °C). The TiO(2) film was immobilized on glass spheres and the powder was characterized by scanning electron microscopy (SEM), X-ray diffraction and BET. This characterization suggested that thermal treatment did not introduce substantial changes in the measured microstructural characteristics of the photocatalyst. The immobilized photocatalyst degraded more than 96% of the MB in up to 90 min of reaction. The photocatalytic activity decreased after four photocatalytic cycles, but it was recovered by the removal of contaminants adsorbed on the active sites after washing in water under UV-Vis irradiation. Based on these results, the TiO(2)-400 °C coated on glass spheres is potentially a very attractive option for removal of persistent contaminants present in the environment.